Pengembangan Tekstil Berbasis Motif dan Nilai Filosofis Ornamen Tradisional Sumatra Utara - Daulat Saragi (LP2M ISBI Bandung, 2018)
ABSTRACTEthnicity and cultural diversity of North Sumatra is the pride of the communities who contribute to the wealth of cultural heritage. Nowadays, a textile development has been successfully explored with a variety of ornaments and its philosophical values, and it has been brought into fashion trends. The North Sumatra ornamental motifs contribute to the world of fashion today. Fashion designers pay big attention to the advance of the complexity of ethnic motifs in the development of the textile world. The study was conducted by the method of documentation, observation, and interpretation of the meaning of the motifs. Verstehen method (understanding) is used to interpret the symbols of ornamental motifs containing the ideas of community. The result is an alternative of textile motif development of North Sumatra-based on local patterns. With the richness of textile patterns raised from local ethnic of North Sumatra, make the fashion increasingly popular and in demand, and ultimately contributes to the development of the textile and fashion industry.Keywords: ornamental motifs, philosophical values, textile industry ABSTRAKKeanekaragaman suku dan budaya Sumatra Utara merupakan kebanggaan masyarakatnya yang berkontribusi kepada kekayaan budaya Nusantara. Perkembangan tekstil dewasa ini berhasil mengeksplorasi aneka motif dan nilai filosofis ornamen tradisi dan mengangkatnya menjadi tren mode. Motif ornamen Sumatra Utara telah berkontribusi pada dunia mode saat ini. Perancang busana melirik adanya suatu kekuatan corak etnis yang diangkat menjadi corak secara masif dalam perkembangan dunia tekstil. Penelitian dilakukan dengan menggunakan metode dokumentasi dan observasi, interpretasi atau pemaknaan, sekaligus melakukan penafsiran terhadap data yang terkumpul. Metode verstehen (pemaaman) dilakukan terhadap motif-motif ornamen sebagai simbol yang mengandung ide-ide masyarakatnya. Hasil penelitian menjadi alternatif pengembangan motif tekstil Sumatra Utara yang berbasis corak lokal. Dengan semakin kayanya corak tekstil yang diangkat dari etnis lokal Sumatra Utara akan menjadikan dunia fesyen semakin digemari dan diminati, dan akhirnya berkontribusi terhadap perkembangan industri tekstil dan fashion.Kata kunci: Motif ornamen, nilai Filosofis, industri tekstil